The design of dust barriers to reduce collector mirror soiling in CSP plants - Sansom, Christopher L.; King, Peter; Fernández-García, Aránzazu; Almond, Heather; Kayani, Talib; Boujjat, Houssamme (American Institute of Physics (AIP), 2018)
In this work we investigate, design, and evaluate a number of dust barrier designs that would be appropriate to reduce soiling of glass mirror solar collectors in the solar field of an existing CSP plant. The principal objective was to reduce the amount of soiling (and hence the amount of cleaning water consumed) by 50% in comparison with current cleaning procedures (considering particles of size >25 µm). “Fluent” CFD software was used to model of a range of potential dust barrier shapes, sizes, and porosities. Airflows and wind loadings were analyzed in this way. A number of potential designs were then taken forward for experimental validation. Initial validation involved wind tunnel evaluation of a small number of potential designs, using a new wind tunnel specifically designed and built for this project. Larger-scale outdoor validation was carried out both at Cranfield University in the UK and at CIEMAT-PSA (Plataforma Solar de Almeria) in Spain. Initial results were independent of location and barrier shape and showed that the percentage of particles that were stopped completely or travelled less than 1m beyond the barrier was in the range 45.8 ± 5%.